ORGANOLEPTIC AND DEGUSTATION EVALUATION OF ORGANIC COCKEREL MEAT - Kucheruk, M. D. (Scientific Progress & Innovations, 2019)
The article provides the evaluation of the meat quality of organic chickens and suggests the breed of chickens that are suitable for producing both meat products and eggs in organic poultry farming. For comparison, the meat of traditionally grown broiler chickens (dressed chickens were purchased in the retail network) and meat of organically grown cockerels (on an organic certified farm) was used. The comparison of the pectoral and femoral muscles’ taste, as well as meat-bone broth, was made. Sample preparation and tasting was carried out according to the standardized analysis. The meat of organic cockerels has high palatability traits. Its significant taste advantage both of white (pectoral muscles) and red (femoral muscles) meat was established. Positive differences as compared with broiler chicken meat concern palatability, aroma, meat, and broth; however, organic cockerel meat has a somewhat denser texture, which gives a special taste to meat. Meat-bone broth obtained by cooking the carcasses of organic cockerels has better organoleptic qualities, and is superior to that obtained from cooking broiler chickens. The studies established the feasibility of using egg-meat breed of chickens in organic poultry farming, since hens are grown to produce eggs and cockerels are not disposed of at the age of one day, but kept in proper conditions on an organic farm to produce meat. Organic chicken meat can be used in children’s and dietary nutrition, since the compliance of keeping conditions and the quality of feeding is monitored by certifying organizations. As far as bio-ethics and humaneness is concerned, the feasibility of growing cockerels for meat using organic feeding and maintenance was substantiated. The meat of broiler chickens in its taste and quality properties is inferior to organic chicken meat. Economically, organic chicken meat will have added value and expenses for certification in many regions of Ukraine will be compensated by the Government. Therefore, rational management and using the appropriate breeds of chickens will contribute to the development of organic production in Ukraine, which is an important step towards ensuring the health of the nation.